Smart forage selection could significantly improve soil health in the tropics - Horrocks, C.A.; Arango, Jacobo; Arévalo, Ashly; Nuñez, Jonathan; Cardoso Arango, Juan Andrés; Dungait, J.A.J. (Elsevier, 2019)
The use of tropical grasslands to graze livestock is of high economic importance. Declining grassland soil health leads to reduced sustainability of livestock systems. There are high levels of phenotypic diversity amongst tropical forage grasses. We hypothesise that this variation could lead to significant differences in soil health and that selection of forage cultivars to improve soil health could improve the sustainability of livestock production. We measured and compared key soil health metrics (soil organic carbon (SOC) concentration and sugar / alkane composition, aggregate stability, friability, litter decomposition rates, microbial community composition) under four tropical forage varieties (Brachiaria hybrid cv Mulato (BhMulato), B. humidicola cv Tully (CIAT679; Bh679), B. humidicola cv CIAT16888 (Bh16888), and Panicum maximum CIAT 6962 (Pmax)) and a bare soil control, there was a significant difference in soil aggregate stability, friability and SOC concentration between the forage varieties with soil under Bh679 and Bh16888 tending to have greater aggregate stability, friability and SOC concentrations compared to the soil under BhMulato and Pmax. We identified significant spatial variation in soils under BhMulato and Pmax due to their tussock forming growth habit; when compared to soil from adjacent to the tussocks, soil from the gaps between tussocks had significantly reduced aggregate stability under both species, significantly reduced friability under Pmax and significantly reduced SOC under BhMulato. We found limited impact of forage variety on soil microbial community composition, litter decomposition rates or soil alkane and sugar concentrations.